PENGARUH ONLINE PROMOTION TERHADAP REPURCHASE INTENTION DENGAN CONSUMER PERCEPTION SEBAGAI MEDIASI PADA TRAVEL ONLINE - Stefanie Adelia (Institute of Research and Community Outreach - Petra Christian University, 2018)
Marketing strategies such as online promotion are now mostly done to attract customer repurchase intention to online travel services by establishing a good consumer perception. Online media is chosen as a media campaign because it is able to reach a very broad market segment and not limited to time with a relatively low cost and can form a consumer perception that affects the consumer's buying interest. Research on the influence of online promotion on repurchase intention with consumer perception as mediation on online travel is done to 100 online travel online buyers selected by non-probability sampling with WarpPLS data analysis technique. The results showed that online promotion has a positive effect on repurchase intention directly and repurchase intention positively indirectly influence through the mediation variable consumer perception. This study proves that consumer perception can be a good mediation between online promotion and repurchase intention